Features of Motivation and Personality in Students in Multicultural Rural Educational Environments - Dekina, E.V.; Shalaginova, K.S. (Psihologo-pedagogičeskie issledovaniâ, 2022)
The article discusses features of motivation and personality in adolescents studying in multicultural schools located in rural ares and offers psychological and pedagogical technologies for the study and prevention of negative phenomena. The materials of an empirical study obtained on a sample of 30 students of 8-9 grades of three rural schools of the Tula region are described. We used the questionnaires developed by ourselves as well as the following techniques: "Scale for assessing the need for achievement" (Yu.M. Orlov), "Motivation for success" (T. Ehlers), "Meaning-of-life orientations test" (D.A. Leontiev), "Lifestyle index" (a questionnaire by Plutchik-Kellerman-Conte). To prevent the negative phenomena in rural adolescents in a multicultural environment, the program "Strive for Change" was developed and tested. It includes the following areas of focused work: self- knowledge and self-development; development of the adolescent community; relationships with peers and adults; involvement in various activities based on the needs and interests of adolescents; actualization of professional self-determination; interaction with the family, class teacher, social worker; promoting the interest in representatives of various nationalities. We also provided several recommendations to teachers and parents on how to establish an appropriate environment for rural adolescents that would promote successful development of their motivation and personality. We suggest that such environment should meet the following requirements: the psychological and pedagogical work should be aimed at shaping the identity of a rural community member; families and schools should join their efforts in supporting traditions and transforming the rural society; any prevention programs and its methodological framework should be based on psychological and educational technologies that take into account the social and individual features of rural adolescents; interactions with adolescents should involve active engagement in socially significant activities based on their interests and abilities. В статье рассматриваются особенности мотивационно-личностной сферы сельских подростков, обучающихся в поликультурной среде, предлагаются психолого-педагогические технологии для изучения и профилактики негативных явлений. Описаны материалы эмпирического исследования, полученные на выборке подростков 8-9 классов в количестве 30 учащихся, обучающихся на базе трех сельских школ Тульской области. Использовались авторская анкета, методики «Шкала оценки потребности в достижении» (Ю.М. Орлов), «Мотивация к успеху» (Т. Элерс), «Смысложизненные ориентации» (Д.А. Леонтьев), «Индекс жизненного стиля» (опросник Плутчика-Келлермана-Конте). Для профилактики негативных явлений сельских подростков в поликультурной среде разработана и апробирована программа «Стремись к переменам», включающая следующие направления работы: самопознание и саморазвитие, развитие детского коллектива, взаимоотношений со сверстниками и взрослыми, привлечение к различным видам деятельности с учетом потребностей и интересов подростков, актуализация профессионального самоопределения, взаимодействие с семьей, классным руководителем, социальным педагогом, формирование интереса к представителям различных национальностей; составлены рекомендации педагогам, родителям по формированию мотивационно-личностной среды сельских подростков. Отмечено, что формирование мотивационно-личностной сферы сельских подростков в поликультурной среде будет проходить более успешно, если психолого-педагогическое воздействие направлено на воспитание качеств члена сельской общины, имеет место интеграция воспитательных воздействий семьи и школы, направленная на развитие традиций, преобразование сельского социума; профилактическая программа и ее методическое обеспечение будут базироваться на психолого-педагогических технологиях, учитывающих социальные и индивидуально-личностные особенности сельских подростков; взаимодействие с воспитанниками будет осуществляться в условиях включения учащихся в социально значимые виды деятельности на основе интересов и способностей детей.